Gesto, lavoro e teoria delle categorie. Per un dialogo tra Peirce e Bloch (Lebenswelt. Aesthetics and philosophy of experience., 2019)
In this paper, I will try to establish a parallel between Charles S. Peirce’s (1839-1914) and Ernst Bloch’s (1885-1977) theory of categories. Both the authors hypothesise a phenomenological foundation for their theory of categories: categories are elements of Experience (according to Peirce) and products of Praxis (according to Bloch). Nevertheless, Bloch’s phenomenology is characterised by a peculiar aspect: according to Bloch, the gestural dimension plays a fundamental role in the Knowledge Process, positing the category of ‘Possibility’. In line with Maddalena’s analyses on the relation between ‘Complete Gesture’ and ‘Work’, I will try to illustrate that the parallel between Bloch and Peirce can be extended, by including the semiotic dimension of gesture.